2021
DOI: 10.1208/s12249-021-01976-1
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Vinyl Alcohol) Cryogel Membranes Loaded with Resveratrol as Potential Active Wound Dressings

Abstract: Hydrogel wound dressings are highly effective in the therapy of wounds. Yet, most of them do not contain any active ingredient that could accelerate healing. The aim of this study was to prepare hydrophilic active dressings loaded with an anti-inflammatory compound - trans-resveratrol (RSV) of hydrophobic properties. A special attention was paid to select such a technological strategy that could both reduce the risk of irritation at the application site and ensure the homogeneity of the final hydrogel. RSV dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Comparing the three formulations (3A2S, 3A2S1G, 3A2S1P) of both preparation methods, the swelling ratio and protein release of all scaffolds were not significantly different ( Figure 1 and Figure 2 ). Glycerin and propylene glycol are highly soluble in water, so they were lost during the swelling and releasing studies [ 59 , 60 ], resulting in no significant difference in swelling ratio and protein release compared to the non-plasticizer formulation. These results were also confirmed by Guadarrama-Acevedo et al [ 61 ] who demonstrated that adding propylene glycol into polyvinylpyrrolidone did not affect the swelling ratio of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the three formulations (3A2S, 3A2S1G, 3A2S1P) of both preparation methods, the swelling ratio and protein release of all scaffolds were not significantly different ( Figure 1 and Figure 2 ). Glycerin and propylene glycol are highly soluble in water, so they were lost during the swelling and releasing studies [ 59 , 60 ], resulting in no significant difference in swelling ratio and protein release compared to the non-plasticizer formulation. These results were also confirmed by Guadarrama-Acevedo et al [ 61 ] who demonstrated that adding propylene glycol into polyvinylpyrrolidone did not affect the swelling ratio of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro testing of wound dressings using an MRI technique as such has been marginal so far, but published studies revealed the potential of these techniques. Previous papers by Górska et al have consistently emphasized the usefulness of MRI for the assessment of important features of hydrogel wound dressings [15,16]. On the example of asymmetric wound dressings obtained by the freezing-drying method, a quantitative assessment of various, spatiotemporal aspects of wound dressing membrane hydration has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging has also been used as one of the methods of characterization of hydrogel wound dressings obtained by the freezingthawing (F-T) technique. It has been possible to catch subtle changes inside the membrane during contact with bulk water, e.g., assessment of mass transport-related phenomena at the molecular-(detection of propylene glycol, confinement effects related to pore size) as well as at the macro-level (swelling) [16]. Nevertheless, these in vitro studies did not seem to have much in common with dissolution testing or with real application conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations